Smallholder coffee farmers’ perceptions of climate variability and the adoption intensity of climate-smart agriculture technologies in Uganda - Diana Kirungi; Joshua Wesana; Haroon Sseguya; Xavier Gellynck; Hans De Steur (International Journal of Agricultural Sustainability)
The current adoption intensity of Climate-Smart Agriculture Technologies (CSATs) among smallholder farmers is below the desired level despite the increasing climate change challenges. This study analysed the perceptions of smallholder coffee farmers towards climate variability and how these influence the adoption intensity of CSATs. A survey was conducted with 226 randomly selected coffee farming households in Luweero district, Uganda. Multivariate regression, Multivariate probit and Poisson regression were used to assess the determinants of farmers’ perceptions of climate variability, the determinants of adoption among the different CSATs and the influence of farmers’ perceptions of climate variability on the adoption intensity of CSATs, respectively. The findings show that smallholder farmers are aware of climate variability, as their perceptions about the increase in temperature and decrease in rainfall align with the available meteorological data. Additionally, farmers’ perceptions of changes in rainfall and temperature, credit access, interaction with an extension worker and access to climate information positively influence their adoption intensity of CSATs. The study recommends that efforts to enhance the adaptive capacity of smallholder farmers should consider enhancing farmers’ climate variability awareness through the provision of climate information, enhancing farmers’ access to credit facilities, and strengthening extension service delivery to support farmers in implementing multiple healthy and environmentally friendly CSATs.